Recent Patents on Concentric Journal Bearings - Zhang, Yongbin (Recent Patents on Mechanical Engineering, 2015)
The paper shows concentric journal bearings formed between smooth shafts and smooth journals registered in patents, which are objected by conventional hydrodynamic lubrication theory. Such bearings can be constructed by physical adsorption or by the boundary slippage. In the inlet zone of the bearing, on the stationary bearing surface, a coating is normally covered so that the lubricant significantly more strongly adheres to that surface or the lubricant slips on that surface; On the stationary bearing surface in the outlet zone, the interaction between the lubricant and the bearing surface is otherwise significantly weaker or stronger. It is a new invention of journal bearing by applying the interfacial adsorption or the boundary slippage technologies. The design method, load-carrying mechanism and friction coefficient results of the bearing are given. The invented bearing possesses the merits of high supporting precision, low friction coefficient and easy manufacturing.
Keywords: boundary film